GEOLOGY OF KADU AND SURROUNDING AREA, JATIGEDE AND JATINUNGGAL DISTRICTS, SUMEDANG REGENCY, WEST JAVA PROVINCE - Alvionita, Azizah Tiara; Sunardi, Edy; Ilmi, Nisa Nurul (Universitas Padjadjaran, 2026)
Administratively, the research area is located in Kadu and its surrounding areas, Jatigede and Jatinunggal Districts, Sumedang Regency, West Java Province. This study aims to determine the geological conditions and geological history of the research area. The research method consists of three stages: literature study, field observation for data collection, and studio observation combined with laboratory analysis. Based on geomorphological aspects, the research area is divided into three geomorphological units, namely moderately steep denudational low hills, steep structural elongated hills, and very steep structural sedimentary hills. Field observations indicate that the lithostratigraphic units are grouped into four units arranged from oldest to youngest: claystone unit (Sbl), sandstone unit (Sbp), tuff unit (St), and volcanic breccia unit (Sbv). The claystone and sandstone units were deposited simultaneously during the Middle Miocene in a deep marine environment. Subsequently, during a slightly younger period, the tuff unit (St) was deposited conformably with the sandstone unit. Geological structures developed in the study area include anticline and syncline folds formed in the Late Miocene due to compressional tectonic activity, with the principal stress direction trending northeast–southwest. Other structures such as joints and indications of strike-slip faults are also observed. The volcanic breccia unit (Sbv) was deposited from ancient volcanic eruptions in a disconformable relationship with the claystone unit (Sbl) during the Late Pliocene. Geological resources in the study area include andesite quarrying as well as tourism potential at Mount Jagat and the Pine Forest. The main geological hazard in the area is landslides.